2017
DOI: 10.5539/jas.v9n11p242
|View full text |Cite
|
Sign up to set email alerts
|

Production of Hydroponic Lettuce under Different Salt Levels of Nutritive Solution

Abstract: The objective of this study was to evaluate the effects of different levels of salinity on the production of two cultivars of crisp lettuce under hydroponic cultivation. The research was performed in a protected environment at the Federal University of Campina Grande (UFCG), state of Paraíba, during in the period from 1 to 22 September 2016. The experimental design was completely randomized (CRD) which involved 4 × 2 factorial scheme with four levels of electrical conductivity of the nutrient solution (1.6, 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Pasternak et al [26] concluded that there were significant differences between the fresh weight of cultivars of romaine and iceberg lettuces when EC levels were 8.2 or 10.5 dS/m, respectively. Growth was inadequate at 5.6 and 7.6 dS/m EC levels in an NFT (nutrient film technique) system with iceberg lettuces [27]. The decrease in the numbers of leaves, leaf area, and biomass were linear with the elevation of the EC level (0.5-4.5 dS/m) [28].…”
Section: Introductionmentioning
confidence: 96%
“…Pasternak et al [26] concluded that there were significant differences between the fresh weight of cultivars of romaine and iceberg lettuces when EC levels were 8.2 or 10.5 dS/m, respectively. Growth was inadequate at 5.6 and 7.6 dS/m EC levels in an NFT (nutrient film technique) system with iceberg lettuces [27]. The decrease in the numbers of leaves, leaf area, and biomass were linear with the elevation of the EC level (0.5-4.5 dS/m) [28].…”
Section: Introductionmentioning
confidence: 96%